Streetscape Characteristic of The Coastal Area - P. Egam, Pingkan; M. Rengkung, Michael; M. Rompas, Leidy; H. Thambas, Arthur (Devotion : Journal of Research and Community Service, 2024)
The city corridor is a strategic area with its own aesthetic and functional value. In connection with the city's beauty, streetscape is one of the determining aspects in terms of architecture and spatial planning. The existence of streetscape tends to be overlooked, resulting in the area lacking identity. The presence of streetscape with character can provide a strong identity for the area, especially when the corridor in question has strategic value in terms of function and location. Proximity to the coastal area is indeed one of the advantages, although currently, it is still hidden, especially architecturally. This research aims to analyze streetscape elements with a coastal area approach. The research location is in the corridor of Piere Tendean Street, Manado, divided into 3 segments. The observed units include pedestrians, street furniture, activities, and buildings on the roadside. The conclusion is obtained that there are soft elements, hard elements, mobile elements, and natural elements. Elements closely related to the coastal area are mobile elements, such as activities enjoying the beauty of the beach equipped with breakwaters, activities in pedestrian and park locations, as well as fishing activities conducted in the empty space where the river meets the beach.